1989
DOI: 10.1093/nar/17.21.8783
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an amplification promoting DNA sequence from the hypotrichous cilateStylonychia lemnae

Abstract: The macronucleus of the hypotrichous ciliate Stylonychia lemnae contains a 1218 bp long DNA molecule which becomes highly amplified during vegetative growth due to a continuous overreplication over a long time range. The region which is located upstream the open reading frame of the overamplified 1.2kbp Stylonychia DNA molecule enabled plasmids containing an inefficiently transcribed thymidine kinase gene to persist and amplify upon transfection into mouse L fibroblasts under selective conditions. This region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The sequencing strategy is illustrated in Figure 1. Sequence analysis of complete gene-sized DNA molecules of Stylonychia lemnae revealed that in general the AT content of the subtelomeric regions is significantly higher than in the coding regions, 70-85% for subtelomeric regions, compared to 50-60% for the coding regions (Helftenbein, 1985;Conzelmann and Helftenbein, 1987;Wegner et al, 1989;Wefes and Lipps, 1990;Gaunitz et al, 1992). While the A and T content is about the same in both strands, the G content is in most cases considerably higher than the C content in the 5'-3' strand in both subtelomeric regions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sequencing strategy is illustrated in Figure 1. Sequence analysis of complete gene-sized DNA molecules of Stylonychia lemnae revealed that in general the AT content of the subtelomeric regions is significantly higher than in the coding regions, 70-85% for subtelomeric regions, compared to 50-60% for the coding regions (Helftenbein, 1985;Conzelmann and Helftenbein, 1987;Wegner et al, 1989;Wefes and Lipps, 1990;Gaunitz et al, 1992). While the A and T content is about the same in both strands, the G content is in most cases considerably higher than the C content in the 5'-3' strand in both subtelomeric regions (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…From these data it is obvious that the subtelomeric regions of the macronuclear gene-sized DNA molecules show a common se- T h e two subtelomeric regions of gene-sized DNA molecules were analyzed for the presence of direct repeats, inverted repeats, consensus sequences and palindromic sequences. The table is subdivided into seven columns (left to right): DNA molecule and standard primer used for sequence analysis, inverted repeats at positions 1-10 (since sequences are always presented in 5'-3' direction inverted repeats appear as direct repeats in the table), perfect inverted repeats a t approximately position 40 (the positions in the two subtelomeric regions are given in brackets), sequences resembling the consensus sequence at approximately position 60 (nucleotides identical to the consensus sequence are written in large letters, palindromic nucleotides are written in bold letters), palindromic sequences at approximately position 60 (palindromic nucleotides are written in bold letters), GC-content and G-content of both subtelomeric regions, size of the DNA molecule'-', cyI-and a,-tubulin genes (Helftenbein, 1985;Helftenbein et al, 1989);3-4, p2and p,-tubulin genes (Conzelmann and Helftenbein, 1986;;5, calmodulin gene (Gaunitz et al, 1992); , ribosomal RNA gene (G. Steinbriick, personal comm~nication);~-", 1.0 and 1.4 kb macronuclear DNA molecule (Eder et al, in p r e~s ) ;~: histone H4 gene (Wefes and Lipps, 1990);lo, macronuclear DNA molecule Ma91 (P. Richter, personal communication);", overamplified bend gene (Wegner et al, 1989);12, T-complex protein 1 gene (C. Maercker, personal communication);'3, elongation factor l a gene (Bierbaum et al, 1991);14, ladder gene (H. Fritzenschaf, personal communication);'"'", telomere binding proteins (Fang and Cech, 1991);17, 2.6-kb macronuclear DNA molecule (Stoll et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several independent studies on S. lemnae (Steinbrück 1983;Wegner et al 1989;Kreyenberg et al 1998) and O. nova (Harper et al 1991), a strong increase in some macronuclear minichromosomes was observed under prolonged vegetative growth. Since this macronuclear overamplification is restricted to only a few minichromosomes and overamplified minichromosomes do not contain aberrant telomeres, determination of overamplification may be promoted by internal sequences or structures.…”
Section: Cotransfection Of Two Differently Marked Minichromosomesmentioning
confidence: 97%
“…Other potentially useful elements include the 5′ flanking region (324 bp) of a mouse ribosomal RNA gene that has been shown to promote genomic integration and tandem replication of transgenes89. Other elements of larger size that may help to maintain transgenes in a replicating, episomal state include alpha satellite DNA (∼80 kb), which can serve as a centromeric element, and mammalian origins of DNA replication90–94.…”
Section: Other Fate‐determining Elementsmentioning
confidence: 99%